2001
DOI: 10.1128/mcb.21.7.2423-2434.2001
|View full text |Cite
|
Sign up to set email alerts
|

S338 Phosphorylation of Raf-1 Is Independent of Phosphatidylinositol 3-Kinase and Pak3

Abstract: The Raf-1 serine/threonine protein kinase requires phosphorylation of the serine at position 338 (S338) for activation. Ras is required to recruit Raf-1 to the plasma membrane, which is where S338 phosphorylation occurs. The recent suggestion that Pak3 could stimulate Raf-1 activity by directly phosphorylating S338 through a Ras/phosphatidylinositol 3-kinase (Pl3-K)/-Cdc42-dependent pathway has attracted much attention. Using a phospho-specific antibody to S338, we have reexamined this model. Using LY294002 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 61 publications
7
55
1
Order By: Relevance
“…In accordance with findings by others (31), our data suggest that Rac-1 additionally is involved in the pathway from Ras to the cyclin D1 promoter via the Ras Ͼ Raf Ͼ ERK cascade, presumably by activating p65 PAK-1 (32). The recent suggestion that PAK-3 could stimulate Raf-1 activity by directly phosphorylating Ser-338 through a Ras-phosphatidylinositol 3-kinase/Cdc42-dependent pathway has attracted much attention (48). However, in HC11 cells, this pathway seems to be of minor importance, as the PI 3-kinase inhibitors wortmannin and LY 294002 did not interfere with cyclin D1 induction by Ras (not shown).…”
Section: Discussionsupporting
confidence: 77%
“…In accordance with findings by others (31), our data suggest that Rac-1 additionally is involved in the pathway from Ras to the cyclin D1 promoter via the Ras Ͼ Raf Ͼ ERK cascade, presumably by activating p65 PAK-1 (32). The recent suggestion that PAK-3 could stimulate Raf-1 activity by directly phosphorylating Ser-338 through a Ras-phosphatidylinositol 3-kinase/Cdc42-dependent pathway has attracted much attention (48). However, in HC11 cells, this pathway seems to be of minor importance, as the PI 3-kinase inhibitors wortmannin and LY 294002 did not interfere with cyclin D1 induction by Ras (not shown).…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, the requirement of raft localization for full Raf-1 activity is coupled to Ser-338 phosphorylation, extending previous studies showing that the membranelocalized Ser-338 kinase was required for Raf-1 activation by oncogenic Ras (29). A candidate kinase, PAK, has been proposed (49 -51); however, its role has been challenged (52).…”
Section: Ser-338 Phosphorylation Of Raf-1 Requires Targeting To Raftsupporting
confidence: 52%
“…However, these mutations alone do not activate Raf-1 kinase, implying that phosphorylation of serine 338 may contribute to, but does not determine Raf-1 activation. It has also been suggested that S338 phosphorylation occurs independently of PI3K-dependent PAK activity and hypothesised that other kinases may target this residue (Chiloeches et al, 2001). Both serines are conserved in B-Raf but the counterpart of serine 338 appears to be constitutively phosphorylated (Mason et al, 1999).…”
Section: Pak1 Phosphorylation Of Raf-1 On Serine 338mentioning
confidence: 99%